Immunology: You Remind Me of a Microbe I Know - Soto, Ray (Curr Biol, 2016)
The majority of bacteria found within the gut are commensals, although it is unclear whether these organisms can elicit systemic immunity. New research indicates that gut-microbiota-specific serum antibodies targeting an epitope conserved among Gram-negative bacteria can protect the host from systemic pathogenic infection.